(untitled) - Bateman, Thomas S (Chicago, 1996)
This text is organized around four themes: cost, quality, speed and innovation. It has been updated with current business examples and management research and includes coverage of NAFTA, European unification, strategic alliances and the MBA Enterprise Corps. The book places greater emphasis on entrepreneurship and small businesses and contains 42 new experiential exercises
Keywords: Management